2008
DOI: 10.1007/s00213-008-1216-6
|View full text |Cite
|
Sign up to set email alerts
|

A neurocognitive animal model dissociating between acute illness and remission periods of schizophrenia

Abstract: Rationale-The development and validation of animal models of the cognitive impairments of schizophrenia have remained challenging subjects.Objective-We review evidence from a series of experiments concerning an animal model that dissociates between the disruption of attentional capacities during acute illness periods and the cognitive load-dependent impairments that characterize periods of remission. The model focuses on the long-term attentional consequences of an escalating-dosing pretreatment regimen with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 195 publications
(254 reference statements)
1
34
0
Order By: Relevance
“…Collectively, these studies in mice, rats and primates support the importance of PFC dopamine D 3 receptor activation in the control of cognitive processes involving attentional mechanisms. In a repeated amphetamineinduced model of psychosis and cognitive impairment, sustained attention in an operant task was accompanied by decreased PFC acetylcholine release (Sarter et al, 2009). It is well established that the PFC dopamine D 3 receptors modulate cholinergic neurotransmission (Lacroix et al, 2003;Millan et al, 2007) consistent with this being a potential mechanism for the observed cognitive effects seen in this study.…”
Section: Cns Sites Of Action Of Dopamine D 3 and D 2 Receptors Ligandsmentioning
confidence: 76%
See 1 more Smart Citation
“…Collectively, these studies in mice, rats and primates support the importance of PFC dopamine D 3 receptor activation in the control of cognitive processes involving attentional mechanisms. In a repeated amphetamineinduced model of psychosis and cognitive impairment, sustained attention in an operant task was accompanied by decreased PFC acetylcholine release (Sarter et al, 2009). It is well established that the PFC dopamine D 3 receptors modulate cholinergic neurotransmission (Lacroix et al, 2003;Millan et al, 2007) consistent with this being a potential mechanism for the observed cognitive effects seen in this study.…”
Section: Cns Sites Of Action Of Dopamine D 3 and D 2 Receptors Ligandsmentioning
confidence: 76%
“…This is the first systematic evaluation of the comparative role of dopamine D 2 and D 3 receptors in these behavioral tasks performed by altering the delay between trials such that rats are able (with short) or unable (with long delay) to discriminate; allowing characterization of drugs exerting both positive and detrimental effects on cognitive performance. Furthermore, we previously showed that social recognition is modulated, by dopamine D 3 receptors in the PFC (Loiseau and Millan, 2009) probably reflecting its important role in the top-down control of cognitive processing, which is disrupted in schizophrenia (Baluch and Itti, 2011;Klinkenberg et al, 2011;Noudoost et al, 2010;Rossi et al, 2009;Sarter et al, 2009) and its wellestablish role on working memory. Finally, amphetamineinduced improvement in NOR in an Fmr1 knockout mouse model of Fragile X syndrome correlated with the increase in PFC but not striatal dopamine release measured by microdialysis (Ventura et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Given the continuing debate on the capacity of typical APDs to enhance cognition on the one hand (Buchanan et al 2007;Miyamoto et al 2005;Sarter et al 2008) and the search for cognition enhancing agents for schizophrenia (Buchanan et al 2007;Marder 2006;Marder and Fenton 2004;Stip et al 2005) on the other hand, a model that can distinguish between atypical APDs and cognitive enhancers may have great utility. Our data suggest that at least with regard to some psychotic and cognitive deficits, namely, those that are muscarinic-dependent, cognitive enhancers may offer a better treatment alternative or a useful addition to APDs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have reported the depressive effects of withdrawal, after chronic treatment with escalating doses of amphetamine, on nocturnal locomotor activity and these were accompanied by changes in monoamine concentrations in several brain regions (Robinson and Camp, 1987;Paulson et al, 1991;Paulson and Robinson, 1996). More recently, Sarter et al (2009) have reviewed a series of studies, which reported that amphetamine pretreated rats exhibited impaired attentional capacity during withdrawal periods and when given amphetamine challenges. These impairments were normalized by treatment with haloperidol and clozapine.…”
Section: Models Of Social Withdrawal Involving Pharmacological Manipumentioning
confidence: 95%